1996
DOI: 10.1007/bf01938872
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of copper-zinc superoxide dismutase in trisomy 21

Abstract: Down's syndrome (DS), the most frequent of congenital birth defects, results from the trisomy of chromosome 21 in all cells of affected patients. This disease is characterized by developmental anomalies, mental retardation and features of rapid aging, particularly in the brain, where the occurrence of Alzheimer's disease is observed in trisomy 21 patients over the age of 35. Copper-zinc superoxide dismutase (CuZnSOD) is one of the proteins encoded by chromosome 21 (21q22.1). As a consequence of gene dosage exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 16 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…Although numerous studies have been performed with administration of exogenous SOD1 this 32-kDa protein is not readily internalized within cells, and in the setting of myocardial reperfusion injury variable protective effects were observed (6,(35)(36)(37)(38). There have been reports that increased SOD1 expression can have deleterious effects, and it has even been suggested that modest increases in expression may trigger the abnormalities seen in Down's syndrome (16). With admin- istration of exogenous SOD1 to ischemic tissues it has been reported that dose-dependent toxicity may also occur (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have been performed with administration of exogenous SOD1 this 32-kDa protein is not readily internalized within cells, and in the setting of myocardial reperfusion injury variable protective effects were observed (6,(35)(36)(37)(38). There have been reports that increased SOD1 expression can have deleterious effects, and it has even been suggested that modest increases in expression may trigger the abnormalities seen in Down's syndrome (16). With admin- istration of exogenous SOD1 to ischemic tissues it has been reported that dose-dependent toxicity may also occur (39).…”
Section: Discussionmentioning
confidence: 99%
“…Increased peroxidase activity has been advanced as a possible cause of the familial form of the neurodegenerative disease amyotrophic lateral sclerosis, FALS (9)(10)(11)(12)(13)(14)(15). It has also been suggested that Down's syndrome, trisomy 21, is caused by a 50% increase in SOD1 expression (16). Thus, fundamental questions have been raised regarding the effects of altered SOD1 expression on cellular function and development.…”
mentioning
confidence: 99%
“…. The hSOD1 gene is located on chromosome 21 in q22.1 and the SOD1 enzymatic activity is consequently over-expressed in trisomy 21, or Down's syndrome (DS) persons [1,2]. DS is associated with humoral and cellular immunological abnormalities [3][4][5][6], which are more pronounced in aged patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One of these genes codes for the enzyme SOD 6 . As expected from the gene dose effect, many studies have found an increase in SOD activity of 50% or Annotation more in various tissues of individuals with DS [8][9][10][11][12][13][14][15][16] .…”
Section: Increased Superoxide Dismutase (Sod) Activitymentioning
confidence: 99%